Evaluating Confucius Institute-Nanyang Technological University (CI-NTU) as an instrument of Chinese soft power - Chan, Wei (Nanyang Technological University, 2020)
With China’s growing influence on the international stage, its soft power instruments are attracting closer scrutiny. The establishment of Confucius Institutes (CI) around the world is among one of China’s most controversial soft power instruments to date. While it has faced much criticism in the west, little research has been conducted in Singapore. As such, this paper aims to examine the operations and impacts of CI-NTU to evaluate the effectiveness of the institution in expanding China’s soft power. Through qualitative interviews with CI-NTU graduates, staff members of CI-NTU, and Singaporeans with no pre-existing knowledge of CI- NTU, our findings revealed that CI-NTU is employable as a soft power strategy due to its autonomous operating model that differs widely from other CIs in the world but is limited in the impact that it has on changing perceptions as well as the demographic that it appeals to.